Development of a Batch Type Yield Monitoring System for Grain Combine Harvester - SINGH, MANJEET; SINGH, JASKARAN; SHARMA, ANKIT (Journal of Agricultural Engineering, 2012)
Assessing soil and crop infield variability is crucial and first step of precision agriculture. In precision agriculture, after assessing the in-field variability, the same is taken care of through site-specific planting, site-specific nutrient and other input applications. Batch type yield monitor was developed having load cell of capacity 700 kg with drum size 125x85x80 cm for grain combines to measure the spatial variation of grains for use as single unit or by putting directly in trailer. Combine mounted batch type yield monitor was also developed by fitting an auxiliary tank of size 145Ã—100Ã—85 cm in the main tank and load cell at the bottom of the auxiliary tank. The yield data is displayed over a display unit installed near the driver seat. Yield variability of three different locations having CV of 5.46%, 27.56% and 35.34% were observed during the evaluation of batch type yield monitor. The systems are useful for small and marginal fields because of its low cost and can be used for any crop, or any combine. Yield monitor information can also be geographically referenced for generation of yield maps, which provide year-to-year comparisons of high- and low-yielding areas of a field throughout a crop rotation sequence for better management.